Children's implicit understanding of the stress—illness link: Testing development of health cognitions. Issue 4 (6th October 2016) - Cheetham, Tara J.; Turner‐Cobb, Julie M.; Gamble, Tim
Abstract : Objective: Innate knowledge and developmental stage theory have been used to explain children's understanding of concepts relating to health, illness, and stress. The aim of this study was to investigate the degree to which children demonstrate unconscious cognitive associations between the concepts of stress and illness. Design: The study employed an experimental design using an age appropriate implicit association task. Methods: Thirty‐two children (5–11 years of age) completed the Preschool Implicit Association Test (PSIAT), a computer‐based measure of reaction time to consistent (stress and illness) and inconsistent (stress and health) concept pairings. Results: Whilst age group had a significant effect on reaction times (older children generally displaying faster reaction times than younger children), those as young as 5–6 years of age were able to demonstrate implicit associations between stress and illness using the PSIAT. There was also some indication that this association peaks at around 7–8 years of age. Conclusions: Findings support a combination of developmental stage theory and the innate theory of children's understanding. Whilst sample size is small, this study is the first to apply the PSIAT to the context of implicit cognitive associations between stress and illness in children. Findings have potential implications for the delivery of interventions to facilitate health promotion and development of positive health behaviours in children and indicate that even children as young as 5–6 years have some ability to relate to the concept that stress may influence illness. Statement of contribution What is already known on this subject? The way in which children understand health and illness is commensurate with their developmental stage and experience of illness. Children also appear to have a degree of innate understanding of health and illness and their causes. Furthermore, recent work suggests children have some innate understanding and knowledge of the concept of stress. What does this study add? This is the first study to use an implicit association task to assess children's understanding of stress and illness. Implicit stress–illness associations were seen in children as young as 5–6 years of age. Whilst sample size was small, this proof‐of‐concept study bridges disciplines to further understanding of health.